Filling gaps in the life history of the snapping shrimp Alpheus petronioi: morphology of the first post-embryonic stages reared in laboratory - Pescinelli, Régis Augusto [UNESP]; Costa, Rogerio Caetano [UNESP] (Taylor & Francis, 2022)
Larval characteristics play an important role in life history, phylogenetic and systematic studies. The morphology of the first post-embryonic stages (zoeae I–III) of the snapping shrimp Alpheus petronioi were described in detail and illustrated based on laboratory-hatched larvae. The morphological characteristics of the species were compared with available descriptions of other Alpheus species with known first zoeal stages. We provided a combination of characteristics useful for the diagnosis of the early zoeal stages of A. petronioi. The species can be separated from the first zoeal stage of the other species of the genus using the following structures: basial endite of maxillule with 2 stout spines (both without rows of spinules), and 2 small plumose setae; endopod of maxillule with 1 terminal denticulate seta, 1 short terminal simple seta and 1 subterminal spine; basial endite of maxilla bilobed, with 4 and 5 simple setae on proximal and distal lobe, respectively and basis of second maxilliped with 5 (3 strong and 2 slender) simple setae arranged (2 + 2 + 1). This is the first study on the biology of A. petronioi after its description, adding new information on its life history.
Keywords: Alpheidae; Alpheus heterochaelis; larval development; zoea